If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -3) + 10 = 2(x + -4) Reorder the terms: 3(-3 + x) + 10 = 2(x + -4) (-3 * 3 + x * 3) + 10 = 2(x + -4) (-9 + 3x) + 10 = 2(x + -4) Reorder the terms: -9 + 10 + 3x = 2(x + -4) Combine like terms: -9 + 10 = 1 1 + 3x = 2(x + -4) Reorder the terms: 1 + 3x = 2(-4 + x) 1 + 3x = (-4 * 2 + x * 2) 1 + 3x = (-8 + 2x) Solving 1 + 3x = -8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1 + 3x + -2x = -8 + 2x + -2x Combine like terms: 3x + -2x = 1x 1 + 1x = -8 + 2x + -2x Combine like terms: 2x + -2x = 0 1 + 1x = -8 + 0 1 + 1x = -8 Add '-1' to each side of the equation. 1 + -1 + 1x = -8 + -1 Combine like terms: 1 + -1 = 0 0 + 1x = -8 + -1 1x = -8 + -1 Combine like terms: -8 + -1 = -9 1x = -9 Divide each side by '1'. x = -9 Simplifying x = -9
| 4(4y-47)=y | | 3x-8+8x-9=180 | | 4+4x=x+7 | | 224a^2m^4-14a^2=0 | | 3x+5=24+7x-28 | | a/8=15830 | | (-38)+56-7=11 | | -3(5n+6)=6 | | 6y=186 | | 7b^2-4-27b= | | x+56-7=11 | | -1+4x=-9 | | m/.5=-41 | | 60x+20(400-x)=50(100) | | -x^2+x+50=0 | | 2(0)-9y=-18 | | 4+2x=6-3x | | -x^2-x+50=0 | | x^2-x+50=0 | | 1/6=1/3 | | 6n+5=2n-15 | | d/.5=11 | | 9x-4=7+8x | | 56=12+4x | | s^2+2s+sf+2f=0 | | 8f+9y=2 | | q/2=-1.4 | | 8x-(4x-3)=15 | | x^2+x^2-1=0 | | 5/7d-3/10=4/7d+4 | | 43=-5+8x | | -5.3p=-9-8.9p |